Economic growth and environmental sustainability : the prospects for green growth - Ekins, Paul (Taylor & Francis, 1999)
Ekins breaks new ground in defining the conditions of compatibility between economic growth and environmental sustainability, and provides measures and criteria by which the environmental sustainability of economic growth can be judged.